Acute cerebellar ataxia as a complication of varicella in four children - Kanra, Güler; Yurdakök, Murat; Arslan, Şükrü; Seçmeer, Gülten; Tanyol, Ece; Sarıkayalar, Fikriye (The Turkish Journal of Pediatrics, 1987)
Four cases of acute cerebellar ataxia caused by varicella are presented and the related literature is discussed. Three of the subjects were five years of age and one was nine years of age. There were three females and two males. The patients presented with symptoms of vomiting, tremor and ataxia approximately five or six days after the appearance of typical varicella lesions. Cerebrospinal fluid, EEG, cranial x-ray and computerized tomography findings were all within normal limits. All four patients recovered completely within seven to twelve days after the appearance of neurologic findings without any sequelae.
Keywords: acute cerebellar ataxia; varicella